504 THE USE OF ENDOSCOPIC VACUUM THERAPY (EVT) AS COMPARED TO ENDOSCOPIC STENTING (ES) FOR LEAKAGES AFTER FOREGUT SURGERY. (14th September 2020) - Chan, S; Yip, H; Teoh, A; Chiu, P; Ng, E
Abstract:  : Anastomotic leakage after foregut surgeries are often difficult to manage. The conventional way of endoscopic treatment is ES. However, it carries a risk of stent migration and erosion. EVT is a novel way of treating these leaks. Methods: This was a retrospective cohort study including all patients with anastomotic leak after foregut surgery and were treated with ES or EVT between July 2008 and July 2019. Patients' demographics, type of surgery, size of anastomotic defect, success rate, complications, number of procedures were recorded and compared. Results: There were 17 patients treated with ES and 7 patients treated with EVT. The success rate of both therapies are similar. (11/17(64.7%) in the ES group vs 5/7(71.4%) in the EVT group; p = 0.751). However, there was a trend to less complications in the EVT group (9/17 (52.9%) in ES group vs. 1/7(14.2%) in EVT group; p = 0.135). On the other hand, the EVT group has a trend to requiring more endoscopic procedures (median (range) 3 (7) procedures in the ES group vs 6(11) in the EVT group; p 0.435). Conclusion: The use of EVT is feasible and safe in treating anastomotic leaks after foregut surgeries. Although more procedures are required, it achieved similar success rate while having a trend to less complications.